Management of Small Renal Masses: Literature and Guidelines Review - Antonio Silvestri; Filippo Gavi; Maria Chiara Sighinolfi; Simone Assumma; Enrico Panio; Daniele Fettucciari; Giuseppe Pallotta; Or Schubert; Cristina Carerj; Mauro Ragonese; Pierluigi Russo; Riccardo Bientinesi; et al. (International Brazilian Journal of Urology)
ABSTRACT Renal cell carcinoma (RCC) ranks among the most prevalent malignancies worldwide, with a rising incidence attributed largely to the incidental detection of small renal masses (SRMs ≤ 4 cm) through widespread abdominal imaging. Historically managed with radical nephrectomy, treatment of SRMs has evolved significantly over recent decades. Partial nephrectomy has become the standard surgical approach, while active surveillance (AS) has emerged as a viable alternative for select patients, particularly those with comorbidities or limited life expectancy. AS involves serial imaging to monitor tumor progression, reserving intervention for signs of clinical advancement. This review synthesizes oncological outcomes and current management strategies for SRMs, comparing AS with immediate intervention. A comprehensive literature search (2005–2024) was performed across PubMed, Web of Science, and Scopus, complemented by an analysis of major international guidelines (EAU, AUA, ESMO, CUA, and Latin American Renal Cancer Group). All guidelines support AS for selected patients with cT1a tumors, though criteria vary. The AUA limits AS to tumors <2 cm, while only its guidelines define clear triggers for transitioning from AS to treatment. Imaging surveillance intervals and biopsy indications also differ, with broader support for renal mass biopsy prior to ablation but more selective use during AS. This review underscores the importance of individualized decision-making in SRM management and highlights areas of consensus and divergence among contemporary guidelines.